FAKTOR - FAKTOR YANG MEMENGARUHI KETIDAKPATUHAN MASYARAKAT UNTUK PHYSICAL DISTANCING SELAMA PANDEMI COVID - 19 DI KECAMATAN MEDAN AREA - JODY YUSUF; SITI MASLIANA SIREGAR (LP2MTBM MAKARIOZ, 2021)
COVID-19 is an acute respiratory disease which was discovered on January 30 and is called a public health emergency byWHO. Many people do not want to implement health protocols, especially physical distancing due to several factors.The level of compliance with health protocols itself can be related to sociodemographic, economic, religious and socialfactors. To find out what factors influence community non-compliance in carrying out physical distancing in the Medan AreaDistrict. This study is a quantitative research study with cross-sectional method. Hypothesis testing used is univariate,bivariate with Chi Square, and multivariate logistic regression tests. In this study there were 400 samples.The results showed that during the pandemic the level of community compliance for physical distancing showed 184 peoplewere obedient and 216 were not compliant. Those who do not comply are grouped based on gender, age, education level,ethnicity, worship, and economy. Based on the Chi Square test, the p value for gender factor was 0.155, p value for agefactor was 0.000, p value for education level factor was 0.000, p value for ethnic factor was 0.000, p value for economicfactor was 0.005, and p value for factor of worship was 0.238. Based on the logistic regression test, the Exp. (B) value was35,440 for the education level variable which was the highest value compared to other variables. There are several factorsthat influence community compliance for physical distancing. The factor that has the strongest relationship is the level ofeducation.